ALGORITHM OF DEVELOPMENT OF INTERNATIONAL TRAINING PLAN FOR PREPARATION OF FASHION DESIGNERS WITH ACCOUNT OF INTERCULTURAL COMPETENCE FORMING - Ryabchikova , K.; Nechipor , S. (Problems of Engineer-Pedagogical Education, 2019)
The purpose of this article is to create common approaches to the development of curricula for the training of fashion designers, taking into account the formation of intercultural competencies on the basis of analysis of the basic functions of the activity, a systematic approach to the formation of general and special professional competencies, structural and logical links between the main modules that form competence. The main method in this case was the method of system analysis with nonlinear relationships in the formation of a complex of professional competencies, taking into account the intercultural component. The main criterion is the formation of basic descriptors in the form of knowledge, skills, communications, autonomy and responsibility. Based on the analysis of the curricula for the training of fashion designers in the countries of Europe, Asia, Africa, a non-linear system of forming integral competence has been developed that takes into account the provision of intercultural competence at different stages of preparation for effective work in conditions of other cultures or multicultural environments. The proposed system involves two levels of formation of intercultural competencies in the form of general professional and specially professional part. Formation of intercultural competence can be realized in the form of a sequential, parallel or non-linear elemental scheme. The basic competencies of a specialist in design of clothing are distinguished. They are composed of generally scientific competence, computer and information competence, cultural enlightenment competence, artistic competence, communicative competence with their intercultural parts in addition with common intercultural competence. Highest level include competence in choice of materials, projecting competence, technology competence, organization competence, business competence with their intercultural parts in addition with special intercultural competence. The presented competencies, in combination with intercultural components, are consistent with the main functions of the specialist in the field of design.